Momos advises Zeus: Changing representations of 'Cypria' fragment 1 - Barker, E (S.A.R.G.O.N. Editrice e Libreria, 2008)
This paper investigates the importance of context for assessing fragment one of the ‘Cypria’, one of the poems belonging to an ‘Epic Cycle’ that – along with the Iliad and Odyssey – told the story of the war at Troy. With the exception of the Homeric epics, these poems come down to us in pieces, in the form of mutilated quotations, assorted testimonia and a later summary by Proclus, all of which, by offering brief glimpses of a wider epic world, tend to be mined for glossing the Homeric poems or else for reconstructing the ‘original’ lost narratives. This paper rejects the pursuit of an archetype in favour of tracing the changing representations of the ‘Cypria’ fragment one and exploring the impact of reception on its interpretation. It makes three claims: first, that, from what we can tell from fragment one itself, the ‘Cypria’ potentially belonged to a wider epic world that shared common terminology, themes and strategies with the Homeric poems; second, that the second-century AD summary of Proclus, by means of which the plot of the ‘Cypria’ has come down to us, critically recasts it in relation to, and at the service of, reading Homer; third, that the ‘D-scholion’ to the Iliad, which is our actual source for fragment one of the ‘Cypria’, already betrays the gravitational pull of the Homeric poems, around which the rest of the epic cycle comes to revolve.